Effects of Lifshitz transitions in ferromagnetic superconductors: the case of URhGe - Yury Sherkunov; Andrey Chubukov; Joseph Betouras (2018)
In ferromagnetic superconductors, like URhGe, superconductivity co-exists with magnetism near zero field, but then re-appears again in a finite field range, where the system also displays mass enhancement in the normal state. We present theoretical understanding of this non-monotonic behavior. We explore the multi-band nature of URhGe and associate re-entrant superconductivity and mass enhancement with the finite field Lifshitz transition in one of the bands. We found good agreement between our theory and a number of experimental results for URhGe, such as weakly first order reentrant transition, the dependence of superconducting $T_c$ on a magnetic field, and the field dependence of the effective mass, the specific heat and the resistivity in the normal state. Our theory can be applied to other ferromagnetic multi-band superconductors.